Pyridine nucleotide transhydrogenase PntAB is essential for optimal growth and photosynthetic integrity under low-light mixotrophic conditions in Synechocystis sp PCC 6803 - Kamarainen,J; Huokko,T; Kreula,S; Jones,PR; Aro,E-M; Kallio,P (New Phytologist, 2017)
Pyridine nucleotide transhydrogenase (PntAB) is an integral membrane protein complex participating in the regulation of NAD(P)+:NAD(P)H redox homeostasis in various prokaryotic and eukaryotic organisms. In the present study we addressed the function and biological role of PntAB in oxygenic photosynthetic cyanobacteria capable of both autotrophic and heterotrophic growth, with support from structural three-dimensional (3D)-modeling. The pntA gene encoding the α subunit of heteromultimeric PntAB in Synechocystis sp. PCC 6803 was inactivated, followed by phenotypic and biophysical characterization of the ΔpntA mutant under autotrophic and mixotrophic conditions. Disruption of pntA resulted in phenotypic growth defects observed under low light intensities in the presence of glucose, whereas under autotrophic conditions the mutant did not differ from the wild-type strain. Biophysical characterization and protein-level analysis of the ΔpntA mutant revealed that the phenotypic defects were accompanied by significant malfunction and damage of the photosynthetic machinery. Our observations link the activity of PntAB in Synechocystis directly to mixotrophic growth, implicating that under these conditions PntAB functions to balance the NADH: NADPH equilibrium specifically in the direction of NADPH. The results also emphasize the importance of NAD(P)+:NAD(P)H redox homeostasis and associated ATP:ADP equilibrium for maintaining the integrity of the photosynthetic apparatus under low-light glycolytic metabolism.